An Audit of Patient Characteristics, Contributing Factors, and Outcomes of Patients Leaving against Medical Advice at Sheikh Khalifa Medical City Abu Dhabi - Shamma Salem Alhajeri; Ibrahim Atfah; Ali Bin Yahya; Salama Matar Al Neyadi; Fatema Salem Al Ameri; Nasser Ahmed; Ismail Al Ramahi; Kenneth Charles Dittrich; Hasan Qayyum (Saudi Journal of Emergency Medicine)
Background: Leave against Medical Advice (LAMA) is defined as ‘a decision to leave the hospital before the treating physician recommends discharge'. The prevalence of LAMA has been reported as 0.07% to 20% in emergency departments (ED) worldwide. Leave against Medical advice has also been reported to have higher rates of re-admission, longer subsequent hospitalization, and more importantly worse patient outcomes. In addition to this, they are also associated with poor healthcare resource utilization. We conducted a single center audit to establish the quality of documentation, identify patient demographics, contributing factors, and outcomes of patients leaving against medical advice from our ED. We benchmarked our data against locally available SEHA clinical policy guidelines. Objectives: The primary aim of this audit was to evaluate the demographic and socio-economic characteristics of patients who opt for LAMA, identify contributing factors in patients who opt for LAMA, and benchmark our current practice against a SEHA policy guideline (Policy no. C-MD-GEN-01-024). Methods: We analyzed the electronic health records at Sheikh Khalifa Medical City, Abu Dhabi, for ED patients who signed LAMA between 2018 and 2023, selecting a convenience sample of 120 patients. Based on a literature review, we identified patient demographics, possible contributing factors, and patient outcomes to evaluate. Results: With a sample of 120 patients, we discovered that the majority of cases presented in the evening and nighttime (97 patients; 80.8%).57 (47.5%) patients had an ED length of stay of 3 hours or more and the average ED length of stay for these patients was 3.4 hours. From a demographic aspect, 93 patients (77.5%) were at age 16 years and above. 73 patients (60.3%) of the entire sample had health insurance coverage. The commonest reason for signing LAMA was a social reason in 45 (37.5%) cases. In the remaining cases, the causes were a combination of family, financial, waiting, or other/undocumented reasons). Conclusion: To summarize, when addressing LAMA situations involving patients or their caregivers thorough discussions must occur and be documented in the LAMA*ER powernote. A formal assessment of capacity is expected to be conducted, and thorough documentation of the process is crucial from a medicolegal perspective. Pursuing the assistance of a Public Relations Officer (PRO) is advisable in handling these cases. ED Physicians must familiarize themselves with the UAE's Wadeema Law, particularly its implications for child safety. For children under 18 years old, LAMA is not applicable in unstable or life-threatening conditions; security can be informed to involve the police if required. It is recommended that all frontline healthcare workers know how to reach their healthcare facility's paralegal team for further assistance. [SJEMed 2024; 5(1.100): S40-S41]